PENGKAJIAN PARAMETER FUNGSI VOLUME POHON MELALUI FOTO UDARA DI KALIMANTAN TIMUR - Ishak Sumantri; Haryono Haryono; Machfudh Machfudh (Jurnal Penelitian Hasil Hutan, 1984)
The relationship  between   tree crown  diameter  and/or  tree height which  measured from aerial photos in tropical rain forest is the  object  of this  study. Result of model  analysis  by crown  diameter  and  tree height  variable are as follows   :In  the  harvested primary  forest  condition, the  most  appropriate  model  for all tree samples  is :   Y  =   30,615 -1,580 D + 1,247 T + 0,037 D2 -0,021 DT               with  coefficient   correlation  r =  0,9637.The  most  appropriate  model  by  crown  diameter  variable in the  harvested   primary  forest  condition   for all trees samples  is  :           Y = 1,732  + 0,214 D  with  r =  0,2971.          For Meranti  species,  the  most  appropriate  model  is :          Y = 6,684 - 0,555 D + 0,020 D2 with  r = 0,664  and for Ulin species is:          Y = -  37,736 + 2,738 D -  0,036 D2  with  r = 0, 776.      3. The  model  and  its analysis are valid for  East Kalimantan  only.